2002
DOI: 10.1002/humu.10117
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic implications from DNA polymorphism in random human genomic sequences

Abstract: Denaturing high performance liquid chromatography (DHPLC) in combination with dye-terminator sequencing was used to survey 516 random genomic sequence tagged sites (STSs) for biallelic polymorphisms in 24 representatives of the major ethnic groups residing in the United States. Of the 301 polymorphic STSs (58.3%), 172 contained a single simple sequence polymorphism (SSP), while 78, 35, and 16 contained 2, 3, and 4-6 SSPs, respectively. Of the 541 SSPs identified, 342 (63%), 152 (28%), and 47 (9%) were transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The ratio between nucleotide transitions and transversions (Ti:TV) was in agreement with data from other species, such as man (Wang et al ., 1998) and sugar beet (Schneider et al ., 2001). The average level of nucleotide diversity with π= 0.74 × 10 −3 was in the same range as found for man, where π varies between 0.4 × 10 −3 and 1 × 10 −3 (Cargill et al ., 1999; Shastry, 2002; Shen et al ., 2002; Sunyaev et al ., 2000; Wang et al ., 1998). The molecular diversity of the total potato germ plasm pool analysed in this study was lower than the values reported for grass species such as rice, barley, wheat, sorghum, pearl millet and maize (reviewed in Buckler et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between nucleotide transitions and transversions (Ti:TV) was in agreement with data from other species, such as man (Wang et al ., 1998) and sugar beet (Schneider et al ., 2001). The average level of nucleotide diversity with π= 0.74 × 10 −3 was in the same range as found for man, where π varies between 0.4 × 10 −3 and 1 × 10 −3 (Cargill et al ., 1999; Shastry, 2002; Shen et al ., 2002; Sunyaev et al ., 2000; Wang et al ., 1998). The molecular diversity of the total potato germ plasm pool analysed in this study was lower than the values reported for grass species such as rice, barley, wheat, sorghum, pearl millet and maize (reviewed in Buckler et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore took a global perspective in our study of nsSNPs by testing 16 different populations. Published studies on the question of human genome evolution have begun to identify genes and regions marked by evidence of selection [Tishkoff et al, 1996;Salamon et al, 1999;Huttley et al, 2000;Akey et al, 2002;Osier et al, 2002;Sabeti et al, 2002;Shen et al, 2002;Gilad and Lancet, 2003;Kayser et al, 2003;Rockman et al, 2003;Akey et al, 2004;Bersaglieri et al, 2004;Hahn et al, 2004;Storz et al, 2004;Hughes et al, 2005;Stajich and Hahn, 2005], such as extreme F ST values and correlations between rates of recombination and nucleotide diversity. According to these data, recent selection seems to have substantially affected many regions of the human genome; however, more needs to be done to fully understand this phenomenon.…”
Section: Introductionmentioning
confidence: 98%
“…However, findings from recent population genetics studies suggest the possibility that selective fertility, nonrandom mating, drift, and other violations of the Hardy-Weinberg equilibrium accelerated genetic divergence between modern human populations, particularly since humans began farming and civilization developed (3)(4)(5)(6). Extending this logic, rapid economic development and the corresponding demographic transition over the past two centuries may have led to a further shift in the dynamics of reproduction and selection.…”
mentioning
confidence: 99%